Force control improvements in chronic stroke: bimanual coordination and motor synergy evidence after coupled bimanual movement training - Kang, Nyeonju; Cauraugh, James H. (Experimental brain research, 2014)
Bimanual movement disorders are common dysfunctions post stroke. This stroke study investigated bimanual force control capabilities to determine the effect of coupled bimanual movement training on bimanual coordination and motor synergy. Stroke participants ( N = 11) completed three bimanual force control tasks at 5, 25, and 50 % of maximum voluntary contraction before and after coupled bimanual movement training. Root mean square error (RMSE), approximate entropy, correlation, and bimanual motor synergy were analyzed in two-way completely within-subjects ANOVAs (Test Session × Force Level: 2 × 3). Multiple linear regression analysis determined the relationship between RMSE and other force control measures. The analyses revealed three important findings: (1) RMSE decreased from baseline to posttest (2) negative correlation (e.g., error compensation) and bimanual motor synergy increased at 25 and 50 % after rehabilitation, and (3) increased bimanual motor synergy was strongly associated with decreased RMSE after training. The findings indicate that coupled bimanual movement training improved force control performance, bimanual coordination, and motor synergies. Indeed, the present findings extend bimanual motor synergies as a meaningful indicator for estimating task performance improvements. Finally, bimanual force control is a valid outcome measure in quantifying progress toward motor recovery post stroke.